Self-forming dynamic membrane filtration for drinking water treatment - Celik, Suna Ozden; Tufekci, Nese; Koyuncu, Ismail (IWA Publishing, 2021)
Abstract Lab-scale continuous operation of self-forming microfiltration (MF) or ultrafiltration (UF) dynamic membranes were investigated simultaneously by applying iron oxide as an alternative treatment option in those waters having natural organic matter (NOM), iron and manganese. Both dynamic membranes gave high removal rates and effluent concentrations of pollutants were below the limit values in synthetic water. 60 and 62% (of DOC) and 75 and 78% (of UV254) were removed in low dissolved organic carbon (DOC) synthetic (LS) water by MF and UF dynamic membranes, respectively. Although only 42 and 49% (of DOC) and 48 and 53% (of UV254) could be removed by MF and UF dynamic membranes, respectively, a remarkable effect on fouling alleviation was observed in high DOC synthetic (HS) water. Iron oxide did not enhance the removal of organic matter in low DOC natural (LN) water as much as it did in synthetic water. Iron oxide led to the removal of high molecular weight organics, thus reversible fouling was reduced almost 2 orders of magnitude through both types of dynamic membranes in high DOC natural (HN) water. Reversible and irreversible resistances were reduced by iron oxide to some extent in LN water. Nevertheless the effect of iron oxide on fouling alleviation was much higher in HN rather than in LN water.
Keywords: iron oxide; fouling; Performance; Ultrafiltration; DOC; River, lake, and water-supply engineering (General); In-Line Coagulation; Ceramic Microfiltration; TD201-500; TC401-506; Water supply for domestic and industrial purposes; removal; doc; Nanofiltration; Natural Organic-Matter; dynamic membrane; Iron-Oxide; Adsorption; Removal; Uf